Intelligent Mobile Olfaction of Swarm Robots - Siti Nurmaini; Bambang Tutuko; Aulia Rahman Thoharsin (Institute of Advanced Engineering and Science, 2013)
This work presents intelligent mobile olfaction design and experimental results of intelligent swarm robots to detection a gas/odour source in an indoor environment by using multi agent based on hybrid algorithm. We examine the problem for deciding when, how and where the gas/odour sensor should be activated. Simple form of cooperation between Interval Type-2 Fuzzy Logic and Particle Swarm Optimization (IT2FL-PSO) algorithm is implemented in the olfaction strategies. The real experiments performed on smaller five mobile robots equipped with dynamic gas/odour sensor TGS2600 and three infra-red sensors. The results show that single robot-based olfaction system with 5 behaviors capable for searching source of a simulated chemical leak in unknown environment and flooking behavior can be done by 3 robots to find the source of gas/odour.